PERADABAN ISLAM DI INDIA-PAKISTAN - Mu'ammar Zayn Qadafy (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2015)
India - Pakistan became one of the great thinkers of Islam contributor. However , there is a big difference on the presence of Muslims in the two countries. This article was written to reveal the history of Islam and Islamic patterns in India and Pakistan as well as to the development of Islam in terms of aspects of science, socio-political and economic circumstances. It was concluded that the difference in the state of Muslims in the country are caused by two different state constitution . Muslims in India especially has experienced a series of setbacks of civilization, is inversely proportional to Pakistan which was established with the spirit of Islam and the Muslims prosper. However Pakistan which is predicted to be able to become an Islamic state monster, until now have not been able to counter India's economic and social terms.